Effect of Bambara groundnut (Vigna subterranea (L.) Verdcourt) varieties on development of Callosobruchus maculatus Fab. (Coleoptera: Bruchidae) - Dauda, Z.; Ayertey, J.N.; Boateng, B.A. (Journal of Arid Agriculture, 2009)
The development of Callosobruchus maculatus Fab. on five varieties (Botosinkpila, Sinkpikara, Sinkpibia, Sinkpipiela and Sinkpisabla) of stored bambara groundnut (Vigna subterranea (L.) Verdcourt) seeds was assessed in the laboratory, under fluctuating temperature and relative humidity of 25.3 to 30.3˚C and 26.7 to 75% R.H. Fifteen grammes 15g of seeds of each variety treatment were weighed separately into 500ml bottles and infested with four pairs (male and female) of 0-48 hrs old adult beetles. Each treatment was replicated 5 times. The number of adults that emerged from eggs was lower than the number of eggs laid on seeds of each variety; however, the emerging progenies were on average much lower in the resistant varieties relative to the susceptible ones. Varieties Sinkpibia, Sinkpipiela and Sinkpisabla were relatively susceptible to infestation by the beetle. Higher numbers of adults emerged from these seeds. The susceptible varieties also suffered more than 50% weight loss after 3 months of storage. Their susceptibility index values ranged from 13-14. Botosinkpila and Sinkpikara varieties produced relatively fewer adults which caused less than 50% weight loss. Susceptibility indices of 12-13 were recorded for these and suggest them to be moderately resistant or tolerant to attack. The two resistant varieties had hard seed coats, with seed coat force values greater than 20 Newton (N) as compared to the soft in the susceptible varieties which had force values of less than 20 N. The significance of these findings to the resource-poor subsistence farmers is discussed
Keywords: Bambara groundnut; Callosobruchus maculatus; resistant; susceptible; seed